Perkembangan Pelabuhanan Merak Sebagai Pusat Perdagangan dan Pelayaran di Indonesia 1912-2009 - Putri, Viona Audia; Susnayanti, Susnayanti; Purnomo, Budi (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
The Merak crossing port route, which connects the islands of Java and Sumatra and is in the city of Cilegon in the province of Banten and is also the busiest crossing in Indonesia, serves as a traffic gateway. In 1912, Merak Harbor saw its first use. Merak Harbor was a spearheading ship port underlying 1912 by the Dutch East Indies government. Before becoming a national asset of Indonesia, the port served colonial political purposes when it was built. The presence of this port is a financial resource for Banten region which has an ocean transportation strategy heading with the point and objective of turning into "the pre-prominent port territory in Indonesia". The reason for this study is to figure out the idea of the improvement of the Merak port as an exchange and delivery focus. Heuristics, source criticism, interpretation, and historiography are the four stages of the method used to write this research. This study relied on books, documents, and journals related to the port of Merak as sources from literature studies that included technical historical analysis based on interpretations of historical facts. The consequences of the review show that the Port of Merak is as yet dynamic in trading merchandise abroad, the presence of the Merak Crossing Port likewise extensively affects the encompassing local area.